Direct and metal-free arylsulfonylation of alkynes with sulfonylhydrazides for the construction of 3-sulfonated coumarins. Issue 4 (25th November 2014) - Wei, Wei; Wen, Jiangwei; Yang, Daoshan; Guo, Mengyuan; Wang, Yingying; You, Jinmao; Wang, Hua
Abstract : A novel and metal-free procedure has been developed for the construction of sulfonated coumarins via direct arylsulfonylation of alkynes with sulfonylhydrazides. Abstract : A novel and metal-free procedure has been developed for the construction of 3-sulfonated coumarins via the direct difunctionalization of alkynoates with sulfonylhydrazides. The present protocol, which simply utilizes TBAI as the catalyst and TBHP as the oxidant, provides a convenient and highly efficient approach to construct a series of sulfonated coumarins with high regioselectivity and good functional group tolerance.